The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.4236/aar.2012.12004
|View full text |Cite
|
Sign up to set email alerts
|

New antioxidant SkQ1 is an effective protector of rat eye retinal pigment epithelium and choroid under conditions of long-term organotypic cultivation

Abstract: Cells have intrinsic mechanisms for cleaning harmful oxidants represented mainly by reactive oxygen species (ROS). Despite the antioxidant defense, ROS can cause serious damage to the retina that with age leads to various eye diseases and even blindness. Among numerous cell sites of ROS generation, mitochondrial electron transport is of crucial importance. Recently, for the purpose of cleaning ROS in the mitochondrial matrix, powerful mitochondria-targeted antioxidant "SkQ1" has been invented. We studied SkQ1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…In our previous study, we have demonstrated the protective effects of the novel penetrating cation 10-(6'plastoquinonyl) decyltriphenylphosphonium, SkQ1, upon RPE and choroid under the conditions of a long-term organotypic culturing of eye posterior cup [13]. Now we have found that 20 nM SkQ1 conserves the native structure and decreases cell death of NR cultivated in the content of eye posterior cup under similar ex vivo experimental conditions.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…In our previous study, we have demonstrated the protective effects of the novel penetrating cation 10-(6'plastoquinonyl) decyltriphenylphosphonium, SkQ1, upon RPE and choroid under the conditions of a long-term organotypic culturing of eye posterior cup [13]. Now we have found that 20 nM SkQ1 conserves the native structure and decreases cell death of NR cultivated in the content of eye posterior cup under similar ex vivo experimental conditions.…”
Section: Discussionmentioning
confidence: 82%
“…The analysis of NR in the content of eye posterior cups was performed after 7, 14 and 30 days of in vitro culturing in a roller, with or without SkQ1 in the medium. 20 nM concentration of SkQ1 was used since previously it inserted positive effects on rat eye tissue viability [13].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At present, neuroprotection strategies aimed at mobilizing endogenous defense systems and enhancing the antioxidant defense of RPE cells remain the most effective [ 272 , 273 , 274 , 275 ]. The RPE is closely associated with the neural part of the retina; therefore, the restoration of photoreceptor functions protects the RPE from OS and vice versa, where the protection of the RPE from OS prevents degenerative changes in the retina.…”
Section: The Exogenous Regulation Of Redox Homeostasis Of Rpe Cellsmentioning
confidence: 99%